Burning Mouth Syndrome: A Review - Sadat, SM Anwar; Chowdhury, Naim Mahmud; Baten, Redwan Bin Abdul (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Burning Mouth Syndrome (BMS) is characterized by chronic oro-facial pain in the absence of specific oral lesions & clinically apparent mucosal alterations. It is more commonly observed in middle aged patients & postmenopausal women. It often affects tongue, cheek, lip, hard & soft palate. Usually symptoms are better observed in morning, worsen during the day and typically subside at night. The condition is multifactorial origin, often idiopathic and its etiopathogenesis remain largely enigmatic. Associated medical conditions may include neurologic and metabolic disorder, gastrointestinal, urogenital as well as drug reactions. BMS are of two types, primary & secondary. Primary BMS is essential or idiopathic where secondary BMS is caused by local, systemic and/or psychological factors. Clinical diagnosis depends on the careful history taking, physical examinations and laboratory findings. Vitamin, Zinc or Hormone replacement therapy has been found to be effective with deficiency of the corresponding factors. The drug therapy with alpha-lipoic acid, capsaicin, clonazepam, benzodiazepines, tricyclic antidepressants, anticonvulsants may be effective in symptomatic treatment of BMS. But the treatment is still unsatisfactory and there is no definitive cure. J Bangladesh Coll Phys Surg 2016; 34(3): 151-159